Upaya dalam Meningkatkan Kemampuan Menulis Permulaan di Sekolah Dasar - Disti Yuni Sari; Lisa Oktariani; Mila Novira (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Beginning writing skills are an important component in children’s language development at the elementary school level. In this article, literature research was carried out with the aim of studying various strategies to improve elementary school students’ initial writing abilities. This article identifies effective methods to be implemented in basic education by analyzing previous studies. These findings will contribute to the development of more efficient writing learning strategies.